Synthesis of Biobased Polyester Polyol through Esterification of Sorbitol with Azelaic Acid Catalyzed by Tin(II) Oxide: A Kinetic Modeling Study - M. R., Kamaruzaman; Chin, S. Y.; Pui, E. C. L.; Prasetiawan, H.; Azizan, N. (American Chemical Society (ACS Publications), 2019)
A sustainable and renewable biobased polyester polyol for polyurethane production was synthesized through the esterification of azelaic acid and sorbitol catalyzed by tin(II) oxide in a batch system. The studies on chemical equilibrium, reaction kinetics and important operating parameters were carried out. The temperature, molar ratio of sorbitol to azelaic acid and catalyst loading were varied in order to determine the best reaction conditions. The polyester polyol synthesized was tested for its fatty acid content through titration. The best operating condition found was at reaction temperature of 433 K, sorbitol to azelaic acid molar ratio of 4:1 and catalyst loading of 2 wt %, yielding 72% azelaic acid conversion after 6 h of reaction. The presence of minute amount of sorbitan and isosorbide inferred the potential of sorbitol-based branched polyester formation with its backbone incorporated with these sorbitol anhydrides. The equilibrium study validated the endothermicity of the reaction. Meanwhile, the kinetic data well fitted to the Langmuir–Hinshelwood Hougen Watson (LHHW) model with the activation energy of 14.43 kJ/mol.